MAKNA KOMUNIKASI KONSELING (Analisis Wawancara Konseling Dari Berbagai Pendekatan Konseling) - Muhammad Ali (Dialogia, 2015)
Abstract: As human being do not be quit of communicate with others, where he represent the core of from social interaction which various intention and pattern consist in it. Old fellow communications with its child will differ in comparison with communications a lecturer with its student. So also will differ also its meaning of communications conducted by politician with its constituent is compared to communications conducted by a counselor with its client. Last type communications become emphasis in this article in the effort articulating communications when brought to domain of counseling. Its meaning will far leave for behind with communications between reporter with its resource person. Although both of the same is using of communications with interview, but communications of counseling not even look for fact about this topic of that studied, but also deeper than meant to communicate itself candidly is, open, esteeming is human of client, which is on its innings for the shake of its problem of faced by client as target of early strarting of a process of counseling. In this article, writer try to deepen farther mean communications of counseling from some approach in theory of counseling, owning elementary difference see communications process of counseling, although them agree about is important of meaning him a communications of counseling. Keywords: Komunikasi, Konseling dan Interaksi.